2018
DOI: 10.3390/su10072549
|View full text |Cite
|
Sign up to set email alerts
|

Development of Test Equipment for Evaluating Hydraulic Conductivity of Permeable Block Pavements

Abstract: Abstract:The use of permeable block pavement has been acknowledged as one of the promising Low Impact Development (LID) strategies to mitigate the harmful effects of depletion of natural surfaces, due to the uncontrollable development of infrastructure and buildings. Numerous studies, associated with drainage properties and long-term performance of this traditional pavement alternative, have been conducted in the past 30 years. Nevertheless, standardized equipment and methodologies are still limited, specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Specimens with dimensions of 0.3 × 0.3 × 0.05 m and porosity of 19.6% were tested. The horizontal permeability was evaluated according to a procedure developed by Ahn et al [23], and the vertical permeability was examined using a constant head procedure presented in Ahn et al [24]. A summary of the two test procedures is presented in Figures 3 and 4 From the experimental results, the horizontal and vertical permeabilities were 11.1 and 9.2 mm/s, respectively.…”
Section: Materials Parametersmentioning
confidence: 99%
“…Specimens with dimensions of 0.3 × 0.3 × 0.05 m and porosity of 19.6% were tested. The horizontal permeability was evaluated according to a procedure developed by Ahn et al [23], and the vertical permeability was examined using a constant head procedure presented in Ahn et al [24]. A summary of the two test procedures is presented in Figures 3 and 4 From the experimental results, the horizontal and vertical permeabilities were 11.1 and 9.2 mm/s, respectively.…”
Section: Materials Parametersmentioning
confidence: 99%
“…and field tests [11,12]. However, their effectiveness as a LID for a specific case has to be estimated at an urban scale, which is usually carried out by numerical simulations carried out with appropriate software.…”
Section: Types Of Pervious Pavements (Pps)mentioning
confidence: 99%
“…PPs have a major role in allowing water infiltration, which improves city resilience to rainfall events [7][8][9][10]. Their hydraulic performance can be assessed by both laboratory and field tests [11,12]. However, their effectiveness as a LID for a specific case has to be estimated at an urban scale, which is usually carried out by numerical simulations carried out with appropriate software.…”
Section: Introductionmentioning
confidence: 99%
“…The fluid velocity in pavement need to be measured however there is limitation in the methodology to measure it. One of recent methodology IOP Publishing doi:10.1088/1755-1315/1135/1/012017 2 introduce by Ahn et al [4], FLOW-3D provided a comprehensive CFD simulation platform to investigate the dynamic behaviour of liquids and gas in a wide range of industrial applications and physical processes. This method was tested in pavement study which is made by Rashid et al [5] and the result shows that there were 5 seconds differences between the observed and computed results using FLOW 3D.…”
Section: Introductionmentioning
confidence: 99%